The Effects of Morphology and Linker Length on the Properties of Peptide–Lanthanide Upconversion Nanomaterials as G2 Phase Cell Cycle Inhibitors. Issue 27 (8th July 2015) - Chan, Chi‐Fai; Xie, Chen; Tsang, Ming‐Kiu; Lear, Sam; Dai, Lixiong; Zhou, Yan; Cicho, Jakub; Karbowiak, Miroslaw; Hreniak, Dariusz; Lan, Rongfeng; Cobb, Steve L.; Lam, Michael Hon‐Wah; et al.
Abstract: In this work, the shape effect of our same‐sized hybrid nanomaterials conjugated with two different Plk1‐specific peptides had been investigated in terms of their photophysical properties, cellular uptake efficiencies, and selective inhibitory effects towards cancer and normal cells. The results clearly indicate that our spherical NaGdF4 @SiO2 ‐P1 nanoparticles achieve the best performance for in vitro imaging, G2 phase cell arrest, and, hence, cell cycle inhibition. Abstract : Plk1‐specific peptides are bioconjugated onto spherical and cubic NaGdF4 @SiO2 nanoparticles, and the inhibitory effects of the hybrid materials towards normal cells and cancer cells are investigated.